Alumina catalyst carrier and preparation method thereof

By constructing a SiO2 protective layer and a CeO2 and ZrO2 multi-heterogeneous interface on the alumina surface, the stability and corrosion resistance problems of the alumina catalyst under extreme working conditions are solved, and the catalyst's resistance to water poisoning and chlorine corrosion is improved.

CN120662288APending Publication Date: 2025-09-19SUZHOU YUNZHAN TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510733947.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Alumina catalysts exhibit high hydrophilicity and low resistance to chlorine corrosion under extreme working conditions such as high temperature, strong corrosion, high humidity or chlorine, which affects the stability and reliability of catalyst performance.

Method used

A dense SiO2 protective layer is constructed by forming Si-O-Al covalent bonds on the alumina surface, and combined with CeO2 and ZrO2 to form a multi-heterogeneous interface, thereby improving the hydrothermal stability and chlorine corrosion resistance of the carrier.

Benefits of technology

The alumina catalyst's resistance to water poisoning and chlorine corrosion in high-humidity, high-chlorine environments is significantly improved, maintaining the catalyst's active site accessibility and reactant diffusion efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the aluminum oxide catalyst carrier and the preparation method thereof, ethyl orthosilicate and cerium oxide are combined with aluminum oxide, a stable Si-O-Al covalent bond is formed on the surface of aluminum oxide, a compact SiO2 protective layer is constructed, direct contact between water vapor and hydroxyl is effectively isolated, and therefore the hydrothermal stability of the carrier is remarkably improved; according to the present invention, with the SiO2 network structure, the SiO2 network structure can effectively fix and disperse the CeO2 nanoparticles and prevent the CeO2 nanoparticles from agglomeration and inactivation, and the Al2O3 can promote the migration of the electrons and the oxygen species at the SiO2-Al2O3 interface so as to provide the second corrosion resistance barrier on the protection layer through the cooperation of the oxygen vacancy introduced by the CeO2 and the excellent Cl ion capture ability, such that the corrosion resistance of the aluminum oxide matrix can be further inhibited; the interface bonding strength is enhanced, so that the water poisoning resistance and chlorine corrosion resistance of the aluminum oxide catalyst in a high-humidity and high-chlorine environment are improved through the dual cooperation of tetraethoxysilane and cerium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to an alumina catalyst carrier and a preparation method thereof. Background Art

[0002] With the continuous improvement of catalytic efficiency and reaction selectivity in industries such as petrochemicals, fine chemicals, and environmental protection, catalyst technology, as a core means of improving industrial process efficiency, has attracted widespread attention. The performance of a catalyst depends not only on the type and distribution of the active metal, but also, to a large extent, on the structural stability, surface chemical properties, and corrosion resistance of the catalyst support. Support materials must operate stably and long-term under extreme conditions such as high temperature, severe corrosion, high humidity, or the presence of chlorine to ensure the reliability and cost-effectiveness of the catalyst's overall performance.

[0003] Alumina, due to its excellent thermal stability, mechanical strength, and specific surface area, is widely used as a catalyst or catalyst support in industrial catalytic processes such as hydrogenation, desulfurization, and catalytic cracking. However, in working conditions involving chlorine-containing reaction atmospheres (such as chlorinated hydrocarbon cracking, hydrodechlorination, and PVC cracking) or high humidity conditions (such as steam reforming and biomass catalytic conversion), alumina exhibits high hydrophilicity and low resistance to chlorine corrosion, affecting the performance of the catalyst.

[0004] Therefore, it is necessary to design an alumina catalyst carrier and a preparation method thereof to solve the above problems. Summary of the Invention

[0005] The present invention overcomes the deficiencies of the prior art and provides an alumina catalyst carrier and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing an alumina catalyst carrier, comprising the following steps:

[0007] Step S1, dissolving ethyl orthosilicate and zirconium oxide in ethanol solvent, adding ammonia water to adjust to neutrality, and stirring to form a transparent sol;

[0008] Step S2, reacting the cerium nitrate solution with urea, and calcining to obtain cerium oxide nanoparticles;

[0009] Step S3, dispersing pseudo-boehmite in an acidic solution, adding a transparent sol and cerium oxide nanoparticles, ultrasonically dispersing the solution, and spray drying the solution to obtain an alumina composite carrier;

[0010] Step S4: mixing the composite carrier powder and the binder, heating them, and pressing them into tablets.

[0011] In a preferred embodiment of the present invention, in step S1, ethyl orthosilicate and zirconium oxide are mixed and dissolved in an ethanol solvent, wherein the mass ratio of ethyl orthosilicate to zirconium oxide is 8-10:1-1.5, and the mass ratio of the mixture of ethyl orthosilicate and zirconium oxide to the ethanol solvent is 1-1.5:8-10;

[0012] The concentration of the ammonia water is 25-28 wt %, and the concentration of the ethanol solvent is 80-85 wt %.

[0013] In a preferred embodiment of the present invention, step S1 includes the following sub-steps:

[0014] Step S11, mixing ethyl orthosilicate and zirconium oxide in a mass ratio of 8-10:1-1.5, dissolving the mixture in an ethanol solvent, and stirring for 10-20 minutes to obtain an acidic mixed solution;

[0015] Step S12, adding ammonia water dropwise to the acidic mixed solution to adjust the acidic mixed solution to neutrality, and controlling the adding rate to be 1-1.5 mL / min;

[0016] Step S13: Stirring is continued at room temperature for 4-6 hours until the neutral mixed solution is converted into a transparent sol.

[0017] In a preferred embodiment of the present invention, in step S2, the concentration of the cerium nitrate solution is 2-5 wt%, and the mass ratio of the cerium nitrate solution to urea is 2-5:45-50.

[0018] In a preferred embodiment of the present invention, step S2 includes the following sub-steps:

[0019] Step S21, mixing 2-5 wt% cerium nitrate solution and urea in a mass ratio of 2-5:45-50, stirring for 10-15 minutes, transferring to a constant temperature water bath, heating to 90±2° C., and stirring at 300-500 rpm for 6 hours to obtain a suspension;

[0020] Step S22, cooling the suspension to room temperature, centrifuging the cooled suspension at 8000 rpm for 10-15 minutes, and washing the cooled suspension alternately with deionized water and ethanol to obtain a precipitate;

[0021] Step S23: heating the precipitate at 120-140° C. and drying it for 12-14 hours to obtain cerium oxide nanoparticles with a particle size of 5-10 nm.

[0022] In a preferred embodiment of the present invention, in step S3, the acidic solution is a 1-5 wt% nitric acid solution, and the mass ratio of pseudo-boehmite to the nitric acid solution is 1-2.5:10.

[0023] In a preferred embodiment of the present invention, step S3 includes the following sub-steps:

[0024] Step S31, dispersing pseudo-boehmite powder in a nitric acid solution at a stirring speed of 500-600 rpm for 2-2.5 hours to form a transparent alumina sol;

[0025] Step S32: adding the transparent sol and cerium oxide nanoparticles to the alumina sol in sequence and stirring for 30-45 minutes to obtain a composite gel;

[0026] Step S33, heating the composite gel at 150-185° C. for 25-45 minutes to obtain a microsphere precursor;

[0027] Step S34: heating the microspherical precursor to a temperature range of 500-550° C. at a heating rate of 1.5-2.5° C. / min and calcining for 4-4.5 hours to form an alumina composite carrier.

[0028] In a preferred embodiment of the present invention, in step S4, heating comprises: drying at 100-120° C. for 6-6.5 h, and calcining at 300-350° C. for 2-2.5 h.

[0029] In a preferred embodiment of the present invention, the mass ratio of the transparent sol, the cerium oxide nanoparticles, and the aluminum oxide sol is 10-12:15-18:70-75.

[0030] An alumina catalyst carrier is prepared using the method for preparing an alumina catalyst carrier described in the above claims.

[0031] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0032] (1) The present invention provides an alumina catalyst carrier and a preparation method thereof, wherein alumina is combined with tetraethyl orthosilicate and cerium oxide to form a stable Si-O-Al covalent bond on the surface of the alumina, thereby constructing a dense SiO2 protective layer, effectively isolating direct contact between water vapor and hydroxyl groups, thereby significantly improving the hydrothermal stability of the carrier, and the oxygen vacancies introduced by CeO2 and the excellent Cl ion capture ability provide a second anti-corrosion barrier on the protective layer, further inhibiting the corrosion of the alumina matrix by chlorides. At the same time, the SiO2 network structure can effectively fix and disperse CeO2 nanoparticles to prevent their agglomeration and inactivation, while Al2O3 promotes the migration of electrons and oxygen species at the SiO2-Al2O3 interface, enhancing the interface bonding strength, and thus the dual combination of tetraethyl orthosilicate and cerium oxide improves the water poisoning resistance and chlorine corrosion resistance of the alumina catalyst in a high humidity and high chlorine environment.

[0033] (2) The present invention provides an alumina catalyst carrier and a preparation method thereof. Alumina is bonded by tetraethyl orthosilicate and cerium oxide. On the one hand, the generated Si-O-Al covalent bonds tightly connect the SiO2 protective layer and the Al2O3 matrix, significantly improving the bonding strength of the interface between SiO2 and Al2O3. On the other hand, dispersed ZrO2 particles are filled in the pore network to support the SiO2 protective layer and Al2O3, effectively limiting the excessive coating of the SiO2 protective layer, maintaining the medium and large pore structure of the carrier, avoiding pore size reduction and mass transfer blockage. At the same time, ZrO2 and CeO2 cooperate to form a Ce-O-Zr-Al multi-heterogeneous interface, which not only promotes ultrafine dispersion and stable anchoring of CeO2, but also introduces additional Lewis acid sites, thereby enhancing the adsorption and activation efficiency of the reactants.

[0034] (3) The present invention forms a SiO2 network with ethyl orthosilicate and firmly bonds ZrO2 to the surface of alumina through Zr-O-Si and Al-O-Zr chemical bonds, which can effectively prevent the sintering and collapse of the alumina pore wall, maintain the openness of the pore channel and the connectivity of the multi-level pore network. At the same time, the dispersibility of SiO2 particles is improved by ZrO2, and they are deposited on the Al2O3 surface in the form of dispersed phase, dots or fine particles, rather than continuous coverage, thereby effectively retaining the original mesopore and macropore structure of alumina, which not only improves the reactant diffusion efficiency of the catalyst, but also ensures the accessibility of the active sites of the catalyst. DETAILED DESCRIPTION

[0035] A method for preparing an alumina catalyst carrier comprises the following steps:

[0036] Step S1, dissolving ethyl orthosilicate and zirconium oxide in ethanol solvent, adding ammonia water to adjust to neutrality, and stirring to form a transparent sol;

[0037] Step S2, reacting the cerium nitrate solution with urea, and calcining to obtain cerium oxide nanoparticles;

[0038] Step S3, dispersing pseudo-boehmite in an acidic solution, adding a transparent sol and cerium oxide nanoparticles, ultrasonically dispersing the solution, and spray drying the solution to obtain an alumina composite carrier;

[0039] Step S4: mixing the composite carrier powder and the binder, heating them, and pressing them into tablets.

[0040] Alumina is combined with tetraethyl orthosilicate and cerium oxide to form stable Si-O-Al covalent bonds on the surface of alumina, constructing a dense SiO2 protective layer, which effectively isolates water vapor from direct contact with hydroxyl groups, thereby significantly improving the hydrothermal stability of the carrier. The oxygen vacancies introduced by CeO2 and its excellent Cl ion capture ability provide a second anti-corrosion barrier on top of the protective layer, further inhibiting the corrosion of the alumina matrix by chlorides. At the same time, the SiO2 network structure can effectively fix and disperse CeO2 nanoparticles to prevent their agglomeration and inactivation, while Al2O3 promotes the migration of electrons and oxygen species at the SiO2-Al2O3 interface, enhancing the interfacial bonding strength. As a result, the dual combination of tetraethyl orthosilicate and cerium oxide improves the water poisoning resistance and chlorine corrosion resistance of the alumina catalyst in high humidity and high chlorine environments.

[0041] In the present invention, in step S1, ethyl orthosilicate and zirconium oxide are mixed and dissolved in an ethanol solvent, wherein the mass ratio of ethyl orthosilicate to zirconium oxide is 8-10:1-1.5, and the mass ratio of the mixture of ethyl orthosilicate and zirconium oxide to the ethanol solvent is 1-1.5:8-10;

[0042] The concentration of ammonia water is 25-28 wt %, and the concentration of ethanol solvent is 80-85 wt %, which ensures that ethyl orthosilicate and zirconium oxide are fully and evenly dissolved, while providing a suitable sol-gel reaction medium.

[0043] The step S1 specifically includes the following sub-steps:

[0044] Step S11, mixing ethyl orthosilicate and zirconium oxide in a mass ratio of 8-10:1-1.5, dissolving the mixture in an ethanol solvent, and stirring for 10-20 minutes to obtain an acidic mixed solution;

[0045] By forming a silicon main skeleton through ethyl orthosilicate, controlling the ratio of silicon source and zirconium source, and introducing an appropriate amount of Zr element into the subsequently generated SiO2 network structure, it helps to form Zr-O-Si and Al-O-Zr bonding structures, thereby improving the interface bonding strength between the alumina substrate and the SiO2 coating, inhibiting sintering and collapse, and enhancing hydrothermal stability and mechanical stability;

[0046] Step S12, adding ammonia water dropwise to the acidic mixed solution to adjust the acidic mixed solution to neutrality, and controlling the adding rate to be 1-1.5 mL / min;

[0047] Neutral conditions promote the hydrolysis of ethyl orthosilicate to form Si-OH, which then undergoes polycondensation to form a Si-O-Si network. At the same time, zirconium oxide also participates in the polycondensation to form a uniform and dense SiO2-ZrO2 composite network.

[0048] Step S13, stirring continuously at room temperature for 4-6 hours until the neutral mixed solution is converted into a transparent sol;

[0049] The formed transparent sol is highly dispersed and has a small particle size, which provides excellent compatibility and uniformity for the subsequent composite with alumina sol and cerium oxide nanoparticles; the small-particle, uniformly dispersed SiO2-ZrO2 precursor is conducive to the formation of a dense and continuous protective layer on the carrier surface, thereby improving the hydrothermal stability of the carrier in high humidity and high temperature environments, and reducing the collapse and deactivation of the catalyst pores.

[0050] In step S1, ethyl orthosilicate is combined with zirconium oxide to form a SiO2-ZrO2 composite network structure, which effectively prevents pore blockage caused by excessive thickness of the SiO2 protective layer. At the same time, the filling effect of zirconium supports the micro-skeleton between SiO2 and Al2O3, maintains the medium and large pore structure of the carrier, and is beneficial to the diffusion of catalyst reactants and the utilization of active sites.

[0051] In the present invention, in step S2, the concentration of the cerium nitrate solution is 2-5 wt%, and the mass ratio of the cerium nitrate solution to urea is 2-5:45-50.

[0052] In step S2, the following sub-steps are included:

[0053] Step S21, mixing 2-5 wt% cerium nitrate solution and urea in a mass ratio of 2-5:45-50, stirring for 10-15 minutes, transferring to a constant temperature water bath, heating to 90±2° C., and stirring at 300-500 rpm for 6 hours to obtain a suspension;

[0054] Urea gradually decomposes during heating to produce ammonia and carbon dioxide, slowly releasing hydroxide ions to induce the hydrolysis and precipitation of cerium ions. By controlling the release rate, the precipitation reaction process is mild, avoiding rapid grain growth, thereby promoting the stable growth of CeO2 crystal nuclei and helping to form a cerium oxide precursor with a narrow particle size distribution and regular morphology.

[0055] Step S22, cooling the suspension to room temperature, centrifuging the cooled suspension at 8000 rpm for 10-15 minutes, and washing the cooled suspension alternately with deionized water and ethanol to obtain a precipitate;

[0056] Step S23: heating the precipitate at 120-140° C. and drying it for 12-14 hours to obtain cerium oxide nanoparticles with a particle size of 5-10 nm.

[0057] In the present invention, in step S3, the acidic solution is a 1-5 wt% nitric acid solution, and the mass ratio of pseudo-boehmite to the nitric acid solution is 1-2.5:10.

[0058] In the present invention, step S3 includes the following sub-steps:

[0059] Step S31: pseudo-boehmite is selected as an aluminum source and dispersed in a dilute nitric acid solution of a certain concentration. Through the adjustment of the acidic medium, the surface hydroxyl groups of the pseudo-boehmite react with protons, and some aluminum ions are desorbed from the surface and then rehydrated to form an aluminum oxide sol. At the same time, dehydration reactions occur between the aluminum hydroxyl groups to form a three-dimensional network precursor colloidal structure.

[0060] Specifically, pseudo-boehmite powder is dispersed in a nitric acid solution and stirred at a speed of 500-600 rpm for 2-2.5 hours to form a transparent alumina sol;

[0061] Step S32: adding the transparent sol and the cerium oxide nanoparticles to the alumina sol in sequence. The silanol groups in the transparent sol and the aluminum hydroxyl groups in the alumina sol are cross-linked, which not only allows the two components to be fully mixed at the physical level but also achieves covalent bonding at the molecular structure level, thereby enhancing the overall structural stability of the three-phase network.

[0062] Then, the cerium oxide nanoparticles obtained in step S2 are introduced and adsorbed on the surface or pore boundary of the sol network composed of SiO2-ZrO2-Al2O3. Under ultrasonic-assisted conditions, the cerium oxide nanoparticles can be highly dispersed to avoid agglomeration, while also ensuring that they can be distributed in a monodisperse or minimally agglomerated state in the final carrier, thereby improving functional uniformity.

[0063] Specifically, transparent sol and cerium oxide nanoparticles are sequentially added to alumina sol and stirred for 30-45 minutes to obtain a composite gel;

[0064] Step S33, heating the composite gel to gradually volatilize the water therein. As the water content decreases, the distance between particles in the system gradually decreases, the interaction is enhanced, and a three-dimensional gel network with a continuous structure is gradually formed;

[0065] Specifically, the composite gel is heated at 150-185° C. for 25-45 minutes to obtain a microspherical precursor;

[0066] Step S34: heating the microspherical precursor to a temperature range of 500-550° C. at a heating rate of 1.5-2.5° C. / min and calcining for 4-4.5 hours to form an alumina composite carrier.

[0067] Under heating conditions, SiO2 acts as the skeleton to form the shell, covering the surface of the composite system and playing an anti-agglomeration role; ZrO2 is interspersed inside the area where the pores are formed, playing a supporting and "bridging" role, effectively inhibiting the collapse of the alumina skeleton during subsequent high-temperature treatment.

[0068] It is worth mentioning that ethyl orthosilicate and cerium oxide are combined with alumina. On the one hand, the generated Si-O-Al covalent bonds tightly connect the SiO2 protective layer with the Al2O3 matrix, significantly improving the bonding strength of the interface between SiO2 and Al2O3. On the other hand, the dispersed ZrO2 particles fill the pore network, supporting the SiO2 protective layer and Al2O3, effectively limiting the excessive coating of the SiO2 protective layer, maintaining the medium and large pore structure of the carrier, avoiding pore size reduction and mass transfer blockage. At the same time, ZrO2 and CeO2 work together to form a Ce-O-Zr-Al multi-heterogeneous interface, which not only promotes ultrafine dispersion and stable anchoring of CeO2, but also introduces additional Lewis acid sites, enhancing the adsorption and activation efficiency of the reactants.

[0069] In addition, the SiO2 network formed by ethyl orthosilicate and ZrO2 are firmly bonded to the alumina surface through Zr-O-Si and Al-O-Zr chemical bonds, which can effectively prevent the sintering and collapse of the alumina pore wall, maintain the openness of the pore channel and the connectivity of the multi-level pore network. At the same time, ZrO2 improves the dispersibility of SiO2 particles and deposits them on the Al2O3 surface in the form of dispersed phase, dots or fine particles, rather than continuous coverage, thereby effectively retaining the original mesopore and macropore structure of alumina, which not only improves the reactant diffusion efficiency of the catalyst, but also ensures the accessibility of the catalyst active sites.

[0070] In the present invention, in step S4, the heating comprises: drying at 100-120° C. for 6-6.5 hours and calcining at 300-350° C. for 2-2.5 hours.

[0071] In the present invention, the mass ratio of the transparent sol, the cerium oxide nanoparticles and the aluminum oxide sol is 10-12:15-18:70-75.

[0072] 1. Implementation

[0073] Example 1:

[0074] Dissolve ethyl orthosilicate in 80 wt % ethanol solvent and stir for 10 minutes to obtain an acidic mixed solution; add 25 wt % ammonia water dropwise to the acidic mixed solution to adjust the acidic mixed solution to neutrality at a dropping rate of 1 mL / min; continue stirring at room temperature for 4 hours until the neutral mixed solution is converted into a transparent sol;

[0075] A 5 wt% cerium nitrate solution and urea were mixed in a mass ratio of 2:45, stirred for 10-15 minutes, transferred to a constant temperature water bath, heated to 90±2°C, and stirred at 400 rpm for 6 hours to obtain a suspension; the suspension was cooled to room temperature, centrifuged at 8000 rpm for 15 minutes, and washed alternately with deionized water and ethanol to obtain a precipitate; the precipitate was heated at 140°C and dried for 12 hours to obtain cerium oxide nanoparticles with a particle size of 5-10 nm;

[0076] Pseudo-boehmite powder was dispersed in a nitric acid solution and stirred at a speed of 500 rpm for 2.5 hours to form a transparent alumina sol; the transparent sol and cerium oxide nanoparticles were sequentially added to the alumina sol and stirred for 45 minutes, wherein the mass ratio of the transparent sol, cerium oxide nanoparticles, and alumina sol was 10:18:70 to obtain a composite gel; the composite gel was heated at 185°C for 45 minutes to obtain a microsphere precursor; the microsphere precursor was heated to a temperature range of 550°C at a heating rate of 1.5°C / min and calcined for 4.5 hours to form an alumina composite carrier;

[0077] The composite carrier powder and the binder are mixed and dried at 120° C. for 6.5 hours, calcined at 350° C. for 2-2.5 hours, and pressed into tablets to obtain an alumina catalyst.

[0078] Example 2:

[0079] The method is substantially the same as the embodiment, except that ethyl orthosilicate is combined with zirconium oxide, as follows:

[0080] TEOS and zirconium oxide were mixed at a mass ratio of 8:1 and dissolved in 80 wt% ethanol solvent, and stirred for 10 minutes to obtain an acidic mixed solution; 25 wt% ammonia water was added dropwise to the acidic mixed solution to adjust the acidic mixed solution to neutrality at a dropping rate of 1 mL / min; and the mixture was stirred at room temperature for 4 hours until the neutral mixed solution was converted into a transparent sol;

[0081] A 5 wt% cerium nitrate solution and urea were mixed in a mass ratio of 2:45, stirred for 10-15 minutes, transferred to a constant temperature water bath, heated to 90±2°C, and stirred at 400 rpm for 6 hours to obtain a suspension; the suspension was cooled to room temperature, centrifuged at 8000 rpm for 15 minutes, and washed alternately with deionized water and ethanol to obtain a precipitate; the precipitate was heated at 140°C and dried for 12 hours to obtain cerium oxide nanoparticles with a particle size of 5-10 nm;

[0082] Pseudo-boehmite powder was dispersed in a nitric acid solution and stirred at a speed of 500 rpm for 2.5 hours to form a transparent alumina sol; the transparent sol and cerium oxide nanoparticles were sequentially added to the alumina sol and stirred for 45 minutes, wherein the mass ratio of the transparent sol, cerium oxide nanoparticles, and alumina sol was 10:18:70 to obtain a composite gel; the composite gel was heated at 185°C for 45 minutes to obtain a microsphere precursor; the microsphere precursor was heated to a temperature range of 550°C at a heating rate of 1.5°C / min and calcined for 4.5 hours to form an alumina composite carrier;

[0083] The composite carrier powder and the binder are mixed and dried at 120° C. for 6.5 hours, calcined at 350° C. for 2-2.5 hours, and pressed into tablets to obtain an alumina catalyst.

[0084] Comparative Example 1:

[0085] Pseudoboehmite powder was dispersed in a nitric acid solution containing 5 wt% of nitric acid, with a mass ratio of pseudoboehmite to nitric acid solution of 1:10, and stirred at 600 rpm for 2.5 hours to form a transparent alumina sol.

[0086] The alumina sol was heated at 150° C. for 45 minutes to obtain a microspherical precursor, and the microspherical precursor was heated to a temperature range of 550° C. at a heating rate of 1.5° C. / min and calcined for 4 hours to form an alumina composite support.

[0087] 2. Performance Testing

[0088] 1. Dynamic Vapor Sorption (DVS) Test

[0089] 50 mg of catalyst powder was dried under vacuum at 120 °C for 12 h to remove residual moisture;

[0090] The temperature was 25 ± 0.1 °C and the humidity range was 0% → 90% RH (10% step, each step was balanced to a mass change rate of < 0.01% / min);

[0091] The mass change at each humidity equilibrium point was recorded using a dynamic vapor sorption instrument, and the adsorption amount at 90% RH was calculated (unit: wt %).

[0092] 2. Chlorine corrosion resistance test

[0093] About 0.5 g of each sample was weighed and spread flat in a quartz boat. The sample was placed in the center of a tube furnace preheated to 600°C. A HCl / N2 mixed gas (10 vol% HCl, gas flow rate 100 mL / min) was introduced. The reaction time was 4 hours. After cooling to room temperature, the sample was removed and stored in a desiccator. The surface Cl 2p peak intensity was analyzed by XPS, and the Cl - Mass percentage.

[0094] 90%RH adsorption capacity (wt%) <![CDATA[Cl - Residual amount (wt%)]]> Specific surface area loss rate (%) Example 1 4.13 2.98 11.37 Example 2 1.75 1.27 7.65 Comparative Example 1 8.35 6.05 22.50

[0095] By comparing Example 1, Example 2, and Comparative Example 1, it can be concluded that the alumina catalyst prepared in Example 2 has the best performance, mainly because tetraethyl orthosilicate and cerium oxide combine with alumina to form stable Si-O-Al covalent bonds on the surface of alumina, constructing a dense SiO2 protective layer, effectively isolating direct contact between water vapor and hydroxyl groups, thereby significantly improving the hydrothermal stability of the carrier, and the oxygen vacancies introduced by CeO2 and the excellent Cl ion capture ability provide a second anti-corrosion barrier on the protective layer, further inhibiting the corrosion of the alumina matrix by chlorides. At the same time, the SiO2 network structure can effectively fix and disperse CeO2 nanoparticles to prevent their agglomeration and inactivation, and thus the dual combination of tetraethyl orthosilicate and cerium oxide improves the water poisoning resistance and chlorine corrosion resistance of the alumina catalyst in a high humidity and high chlorine environment.

[0096] An alumina catalyst carrier is prepared using the method for preparing an alumina catalyst carrier described in the above claims.

[0097] The above description is based on the ideal embodiment of the present invention. Based on the above description, relevant personnel can make various changes and modifications without departing from the technical scope of this invention. The technical scope of this invention is not limited to the content of the specification and must be determined according to the scope of the claims.

Claims

1. A method for preparing an alumina catalyst carrier, characterized in that: The following steps are involved: Step S1, dissolving ethyl orthosilicate and zirconium oxide in ethanol solvent, adding ammonia water to adjust to neutrality, and stirring to form a transparent sol; Step S2, reacting the cerium nitrate solution with urea, and calcining to obtain cerium oxide nanoparticles; Step S3, dispersing pseudo-boehmite in an acidic solution, adding a transparent sol and cerium oxide nanoparticles, ultrasonically dispersing the solution, and spray drying the solution to obtain an alumina composite carrier; Step S4: mixing the composite carrier powder and the binder, heating them, and pressing them into tablets.

2. The method for preparing an alumina catalyst carrier according to claim 1, wherein: In step S1, ethyl orthosilicate and zirconium oxide are mixed and dissolved in an ethanol solvent, wherein the mass ratio of ethyl orthosilicate to zirconium oxide is 8-10:1-1.5, and the mass ratio of the mixture of ethyl orthosilicate and zirconium oxide to the ethanol solvent is 1-1.5:8-10; The concentration of the ammonia water is 25-28 wt %, and the concentration of the ethanol solvent is 80-85 wt %.

3. The method for preparing an alumina catalyst carrier according to claim 2, wherein: In the step S1, the following sub-steps are included: Step S11, mixing ethyl orthosilicate and zirconium oxide in a mass ratio of 8-10:1-1.5, dissolving the mixture in an ethanol solvent, and stirring for 10-20 minutes to obtain an acidic mixed solution; Step S12, adding ammonia water dropwise to the acidic mixed solution to adjust the acidic mixed solution to neutrality, and controlling the adding rate to be 1-1.5 mL / min; Step S13: Stirring is continued at room temperature for 4-6 hours until the neutral mixed solution is converted into a transparent sol.

4. The method for preparing an alumina catalyst carrier according to claim 1, wherein: In step S2, the concentration of the cerium nitrate solution is 2-5 wt%, and the mass ratio of the cerium nitrate solution to urea is 2-5:45-50.

5. The method for preparing an alumina catalyst carrier according to claim 4, characterized in that: In step S2, the following sub-steps are included: Step S21, mixing 2-5 wt% cerium nitrate solution and urea in a mass ratio of 2-5:45-50, stirring for 10-15 minutes, transferring to a constant temperature water bath, heating to 90±2° C., and stirring at 300-500 rpm for 6 hours to obtain a suspension; Step S22, cooling the suspension to room temperature, centrifuging the cooled suspension at 8000 rpm for 10-15 minutes, and washing the cooled suspension alternately with deionized water and ethanol to obtain a precipitate; Step S23: heating the precipitate at 120-140° C. and drying it for 12-14 hours to obtain cerium oxide nanoparticles with a particle size of 5-10 nm.

6. The method for preparing an alumina catalyst carrier according to claim 1, characterized in that: In step S3, the acidic solution is a 1-5 wt% nitric acid solution, and the mass ratio of pseudo-boehmite to the nitric acid solution is 1-2.5:

10.

7. The method for preparing an alumina catalyst carrier according to claim 1, characterized in that: In step S3, the following sub-steps are included: Step S31, dispersing pseudo-boehmite powder in a nitric acid solution at a stirring speed of 500-600 rpm for 2-2.5 hours to form a transparent alumina sol; Step S32: adding the transparent sol and cerium oxide nanoparticles to the alumina sol in sequence and stirring for 30-45 minutes to obtain a composite gel; Step S33, heating the composite gel at 150-185° C. for 25-45 minutes to obtain a microsphere precursor; Step S34: heating the microspherical precursor to a temperature range of 500-550° C. at a heating rate of 1.5-2.5° C. / min and calcining for 4-4.5 hours to form an alumina composite carrier.

8. The method for preparing an alumina catalyst carrier according to claim 1, characterized in that: In the step S4, the heating includes: drying at 100-120° C. for 6-6.5 hours and calcining at 300-350° C. for 2-2.5 hours.

9. The method for preparing an alumina catalyst carrier according to claim 8, characterized in that: The mass ratio of the transparent sol, the cerium oxide nanoparticles and the aluminum oxide sol is 10-12:15-18:70-75.

10. An alumina catalyst carrier prepared by the method for preparing an alumina catalyst carrier according to the above claim.

Citation Information

Cited By

  • Activated alumina ball, preparation method and application of activated alumina ball in sewage treatment

    CN121948995A